Developmental Bibliotherapy with Extremely Shy Children - Çiğdem Kaymaz (Psikiyatride Güncel Yaklaşımlar, 2024)
Extremely shy children may find themselves somehow isolated from society and feel alone. This may cause them to experience different problems at home, at school and in the community. If this situation continues in the following years, the difficulties they experience in life will increase and the probability of their emergence as mental problems such as childhood loneliness, social anxiety disorders, depression and anxiety disorders that negatively affect their quality of life will increase. Thus, it is important to intervene in childhood shyness, social isolation, loneliness, and behavioral inhibition in order to eliminate possible problems that may be experienced in childhood and at the same time to prevent the continuation of the situation in adolescence and adulthood. Developmental bibliotherapy can be used in the context of both prevention and early intervention studies for shyness in early childhood with extremely shy children. In this context, the aim of this study is to provide an in-depth perspective on the concepts of extreme shyness and bibliotherapy, and to present an example of a developmental bibliotherapy session that can be experienced with extremely shy children who are between five to eight years old in early childood period and a sample book list that can be used in the sessions